Medan Fish Centre With Ecological Architecture Approach (International Journal of Architecture and Urbanism, 2022)
Medan Fish Center design is a building design that functions as a fish market which is located on K.L. Yos Sudarso Street, West Medan District, North Sumatra. This design depicts a fish market center equipped with supporting facilities such as a freshwater aquarium, food court, and gallery. The application of ecological architecture to market design applied to the management of liquid waste produced by fish traders. The fish market design is expected to benefit the community not only as a means of the community's economy but also as a means of recreation and education.